ASSISTANCE DIGITAL MARKETING AND BRANDING STRATEGY SUKOHARJO PRODUCT ON MINISTRY OF MICRO SMALL AND MEDIUM ENTERPRISES - Aisyah Mutia Dawis; Renata Fina Antika Cahyani (The Journal Publishing, 2022)
In the era of competition in the world especially, global economy the existence of businesses is expected to boost the economy in indonesia. In this era of competition, MSMEs are required to always improve their competitiveness so that they can continue to run and develop. One of them is by applying information technology and communication a supporting their business activities and continue to do branding. Products. Digital marketing strategy of taking a product information technology where in form of activities and promote their products or services through the medium the internet. Digital marketing are able to increase the income until about 20 %. Therefore, MSMEs are required to always improve their competitiveness. One of them is by applying Information Technology as a support for its business activities. Based on this, the author held digital marketing mentoring activities as a Product Branding Strategy Business at MSMEs in Sukoharjo.